Evaluating the feasibility of transactive approach for voltage management using inverters of a PV plant. (1st June 2021) - Alam, Mollah Rezaul; Alam, M.J.E.; Somani, Abhishek; Melton, Ronald B.; Tushar, Wayes; Bai, Feifei; Yan, Ruifeng; Saha, Tapan K.
Highlights: Feasibility of a voltage management approach in a distribution feeder is studied. A double-auction based transactive control is designed for voltage management. Closed form expression of market clearing var dispatch signal is derived. Real-time demonstration of the proposed approach is provided for a use-case. Simulation is performed in both software-in-loop and hardware-in-loop platforms. Abstract: This article evaluates the feasibility of a double-auction-based Transactive Energy System (TES) for engaging the reactive power (VAR) capability of inverters in a utility-scale photovoltaic (PV) plant for voltage management in distribution feeders. In the proposed approach, a PV plant owner (seller) provides VAR supply curves in terms of price-quantity pairs considering the inverters' P-Q capability, efficiency, opportunity cost for real power curtailment, losses, etc. At the same time, the utility (buyer) proposes VAR demand curves in price-quantity pairs exhibiting the marginal price of VAR. Market clearing points are obtained from the intersection points of supply and demand curves which are then used to create VAR dispatch signals from the PV plant. To conduct a feasibility study of this approach, an Australian distribution network with a utility-scale PV plant (capacity 3.275 MWP ) is modeled in RSCAD and simulated in real-time on MATLAB, RSCAD-RTDS co-simulation platform using real historical data. Considering a use case, namely, conservation voltage reduction (CVR), the operational feasibility along with cost-benefit analysis is demonstrated in software-in-the-loop (SIL) and hardware-in-the-loop (HIL) platform. Another use case, exploring the benefit from the tap-change reduction of step-voltage-regulator, is investigated. These two use cases yield net positive benefit when the partially loaded inverter is engaged to sink VAR without curtailing its real power. These studies explore further use cases, e.g., PV hosting capacity, network reconfiguration, etc., to be incorporated in TES for experiencing substantial economic benefits.